GAMBARAN RESPON YANG DIRASAKAN PETUGAS KESEHATAN TERHADAP PEMBERIAN VAKSIN COVID-19 DI RSUD LABUANG BAJI MAKASSAR - Zulfia Samiun; Jamaluddin Jamaluddin; Nurlina Nurlina (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2022)
The Covid-19 outbreak, which emerged in December 2019 in China, then spread to various countries including Indonesia, so the WHO declared it a global pandemic. Many research institutions and pharmaceutical companies are vying to find and produce vaccines against Covid-19 disease, Indonesia is also involved in the development of COVID-19 vaccines in collaboration with several countries and pharmaceutical companies. Objective: to find out the response felt by health workers to the administration of the Covid-19 vaccine. Method: This type of research is descriptive analytic with descriptive method of the object under study through the collected sample. Methods of data collection with primary data and secondary data. The sampling technique in this research is simple random sampling. Results: there are respondents who feel the effect 5 minutes after the vaccine, there are two respondents who are around 10-15 minutes after the vaccine, there are two respondents who feel the effect 30 minutes after the vaccine, three respondents who are around 1-2 hours after injection, some are 2 hours, there were 3 respondents felt side effects one day after the injection of the Covid-19 vaccine, 2 respondents only felt side effects during the first vaccine, three respondents felt a few hours after the vaccine, one respondent said the effect was felt since receiving the Covid-19 vaccine and there was one respondents who did not feel the effects of the Covid-19 vaccine. Conclusion: The response felt by Health Officers before giving the Covid-19 Vaccine was that respondents felt anxious, stressed, tense, doubtful and afraid. There were 3 respondents who felt normal before receiving the Covid-19 vaccine injection. After receiving the first dose of the Covid-19 vaccine, namely feeling sleepy, hungry, dizzy, headache, sore, achy, cramping at the injection area, feeling anxious about the side effects of the Covid-19 vaccine, and there was one respondent who did not feel any side effects. of the Covid-19 vaccine injection. In the second dose of vaccine, there were respondents who did not feel the same side effects when the first dose of vaccine.Keywords: response, health workers, Covid-19 vaccine